Trifolium repens L. var. repens NGB 19026 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Trifolium repens L. var. repens Common name(s): Trifolium Other names: Valnesfjord AL0512 Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 19026 Method of creation: Acquisition Date: 2008-03-07 Historical: No Biological status: Wild MLS status: Included ...